Upper and Middle Crustal Velocity Structure of the Colombian Andes From Ambient Noise Tomography: Investigating Subduction‐Related Magmatism in the Overriding Plate. Issue 2 (7th February 2018) - Poveda, Esteban; Julià, Jordi; Schimmel, Martin; Perez‐Garcia, Nelson
Abstract: New maps of S velocity variation for the upper and middle crust making up the northwestern most corner of South America have been developed from cross correlation of ambient seismic noise at 52 broadband stations in the region. Over 1, 300 empirical Green's functions, reconstructing the Rayleigh wave portion of the seismic wavefield, were obtained after time and frequency‐domain normalization of the ambient noise recordings and stacking of 48 months of normalized data. Interstation phase and group velocity curves were then measured in the 6–38 s period range and tomographically inverted to produce maps of phase and group velocity variation in a 0.5° × 0.5° grid. Velocity‐depth profiles were developed for each node after simultaneously inverting phase and group velocity curves and combined to produce 3‐D maps of S velocity variation for the region. The S velocity models reveal a ~7 km thick sedimentary cover in the Caribbean region, the Magdalena Valley, and the Cordillera Oriental, as well as crustal thicknesses in the Pacific and Caribbean region under ~35 km, consistent with previous studies. They also display zones of slow velocity at 25–35 km depth under regions of both active and inactive volcanism, suggesting the presence of melts that carry the signature of segmented subduction into the overriding plate. A low‐velocity zone in the same depth range is imaged under the Lower Magdalena Basin in the Caribbean region, which may represent either sublithospheric melts ponding at midcrustal levels after breaching through a fractured Caribbean flat slab or fluid migration through major faults within the Caribbean crust. Key Points: The magmatic signature of the subducting Nazca plate is mapped at midcrustal depths under the central Cordillera Asthenospheric magmas might have breached the Caribbean flat slab through a preexisting vertical tear Fluid migration on major faults might also explain observed low‐velocity anomalies under the Lower Magdalena Basin